TO ANALYZE THE LOVERS OF THE CENTURY WITH REGARD TO THE POSTMODERN POİNT: POSTMODERN BİR KIZ SEVDİM - Bedia KOÇAKOĞLU (International Journal of Eurasia Social Sciences, 2017)
In cultural history, modernism mostly states vicissitudes in art and science in the middle of XIX. century. However, this movement which is gradually spreading and strengthening eventually generates its own reaction. Modernism prevalent in the early 1960s is the name of this reaction. Under favour of postmodernism, the gate of the pluralism was opened and the tradition was brought in. A creativity based on enriching and playing with rules and a broad democratic perspective has emerged by the addition of maxim which adopt irregularity as a principle. Postmodernism on the contrary to modernism which considers populist culture as a deformation breaks away its complexes and has an understanding that adopts the attitude of “have it your way’’ and it attaches importance to the people, history and tradition.In this respect, Süreyyya Evren is one the conspicuous artists (1972-).He who has stories, novels, essays, translations and articles has his first novel Postmodern Bir Kız Sevdim (1993). The writer's novel makes fun by regulating legendary loves to modern-day and in this sense exhibit an ironic approach is like an metafiction blends tradition and postmodernism with a different perspective.Postmodern Bir Kız Sevdim, not only just as the love has turned from traditional to postmodern but also it is such as to emphasize that there is a transition from classical to modern beyond in writing. Within this context, the text is not only a postmodern novel but also remarks itself due to refers to traditional narrations. It can be said that writer parodies these by mostly taking them funny also proved the inter- civilizations variation of love.From this viewpoint, it’s attracted notice that it is noteworthy that in the work of postmodern text, legends from folk literature products such as the folktale are handled with a postmodernist point of view. In the manifesto, Postmodern Bir Kız Sevdim as a new interpretation of traditional texts is going to be evaluatedin this context.